Content and Background Concentrations of Heavy Metals in the Sediment of Urban River in Northern Anhui Province, China - Chen, Song; Fu, Xuehai (Asian Journal of Chemistry, 2013)
The concentrations of 16 chemical elements in the sediment samples from urban river were measured at the northern Anhui province, China. Based on correlation coefficients and regression analysis, the relationships among these elements of 37 sediment samples were studied. The element Al was selected as the reference element for Cr, Zn, V and Cu, while Fe was used as the reference element for Co, Mn, As and Pb. The regional geochemical baseline models of these heavy metals were obtained by the linear baseline model. The background concentrations of these heavy metals were calculated using the selected sediment samples which among the 95 % confidence interval. The result showed that the background were 763, 66.92, 52.84, 238.82, 39.65, 60.18, 28.73 and 13.60 (mg kg-1) for the elements Mn, V, Cr, Co, Cu, Zn, Pb and As, respectively.